THE IMPACT OF CELEBRITY ENDORSEMENT ON PURCHASE INTENTION OF LOCAL SKINCARE BRAND: THE ROLE OF PERCEIVED QUALITY AND PERCEIVED VALUE - Lily Leonita (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2023)
The main objective of this study is to explore the role of celebrity endorsement in generating consumer purchase intent while taking into account perceived value and perceived quality in relation to local skincare brands. in local skincare brands. This study used a survey approach in collecting data. Online research questionnaires were distributed to target respondents. Sampling was carried out using a purposive sampling technique with the criteria of skincare consumers who know local skincare brands and celebrities who endorse the brand. There were 153 responses from respondents that were valid and can be used for analysis. The results of this study demonstrate that the influence of celebrity endorsement and perceived quality on purchase intention is significant. It has been demonstrated that perceived quality helps to moderate the impact of celebrity endorsement on consumers' intention to buy. Celebrity endorsement, moreover, has been shown to influence perceived value. However, perceived value does not affect purchase intention. Hence, it has not been demonstrated that perceived value mediates the impact of celebrity endorsement on purchase or buying intention. The use of celebrity endorsements is able to encourage consumer purchase intentions so that companies should pay attention to the factors in selecting celebrities who will be invited to cooperate to promote products so that the perception of quality as well as the value formed by consumers is in accordance with company targets.